Major Trends in Theoretical and Applied Linguistics 2 - Sougari, Areti Maria (Selected Papers from the 20th ISTAL, 2014)
In the three volumes of Major Trends in Theoretical and Applied Linguistics, the editors guide the reader through a well-selected compendium of works, presenting a fresh look at contemporary linguistics. Aimed at specialists or anyone interested in languages, this publication deals with both theoretical issues and applied linguistics, looking closely at discourse analysis, gender and lexicography, language acquisition and language disorders.